2008
DOI: 10.1063/1.2938843
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of current-driven domain wall motion from pinning sites in nanostrips with perpendicular magnetic anisotropy

Abstract: Current-driven domain wall motion from pinning sites in nanostrips with perpendicular magnetic anisotropy is studied by using micromagnetic simulations, supported by a one-dimensional model of wall dynamics. The threshold current density of perpendicular anisotropy strips is much smaller than that of in-plane anisotropy strips, and is almost independent of the pinning potential strength. This results from the narrower domain wall width, smaller hard-axis anisotropy, and the larger ratio of the depinning field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…In the adiabatic regime, a DW can be depinned when Walker breakdown occurs. Here, not only STT but also the effective field originating from the pinning potential has a significant role in inducing Walker breakdown 19,20 . Consequently, the depinning time is not simply proportional to the inverse of the current (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adiabatic regime, a DW can be depinned when Walker breakdown occurs. Here, not only STT but also the effective field originating from the pinning potential has a significant role in inducing Walker breakdown 19,20 . Consequently, the depinning time is not simply proportional to the inverse of the current (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are mainly two ways to utilize the STT: one is current-induced magnetization switching (CIMS) in magnetic nanopillars 2,[7][8][9][10][11][12] , and the other is current-induced domain wall motion (CIDWM) in magnetic nanowires 1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . In particular, the latter is promising for applications in which a domain wall (DW) moves numerous times within several nanoseconds' duration 4 , or in which numerous DWs are shifted simultaneously 6 .…”
mentioning
confidence: 99%
“…1 W = 40 nm and gap G = 40 nm. Since the DW bend, as mentioned later, would be liable to occur in the strip with wider width, above value was adopted for the W. Material parameters for a PMA thin film 18 were adopted: M s = 600 emu/cm 3 , K u = 4.0×10 6 erg/cm 3 , Gilbert damping constant α = 0.02, non-adiabatic coefficient β = 0.03, polarization P = 0.4. In the present study, local modification of the magnetic properties was assumed as the PS, which can be realized with the local ion implantation 15,16 for example.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Studies have shown the effect of LER on DW depinning in both in-plane magnetic anisotropy (IMA) and perpendicular magnetic anisotropy (PMA) nanowires. [6][7][8][9][10][11] A DW can also be pinned by local variations in anisotropy, which can arise from misorientation between grains in a polycrystalline film or from other perturbations in the nanowire anisotropy, due to inhomogeneous strain for example. 7,12 On the other hand, LER can facilitate the nucleation of a DW or the confinement of a DW to a region within the nanowire, which can be useful in device applications.…”
Section: Introductionmentioning
confidence: 99%
“…8,18 Studies have found that DW pinning fields increase linearly with LER, but narrower linewidths have not been explored. 6,10,19,20 An analytical model has shown the effect of periodic pinning potentials on thresholds for DW traversal. 21 Here, we examine the effects of defects in wires with linewidths below 60 nm, examining both edge roughness and anisotropy variations, on the threshold and on DW velocity.…”
Section: Introductionmentioning
confidence: 99%